Ganglion stellate blockade in the treatment algorithm of the malignant electric storm: one center, five years and 72 procedures in 59 patients. (19th May 2022) - Jiravsky, O; Spacek, R; Chovancik, J; Hudec, M; Miklik, R; Sknouril, L; Stepanova, R; Fiala, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Malignant electric storm (ES) is a life-threatening condition with a high mortality rate. With years of increasing numbers of implanted ICDs, we witness increasing numbers of patients treated for ES. The role of local suppression of sympathetic nerve activity using ultrasound-guided anesthetic ganglion stellate blockade (GSB) is still under investigation with the first favorable published data from prospective cohorts. Objective: To present data from a cohort of consecutive patients treated for ES at our cardiac center using a two-stage algorithm including GSB. Method and Cohort: Between 2017 and 2021, 59 patients were treated using the two-stage algorithm ( when the first stage of standard procedures failed - ions, antiarrhythmic drugs, ischemia correction, heart rate modification, sedation, and GSB was performed as the second stage of the algorithm when ventricular arrhythmia recurred) in 72 GSB procedures. 57 GSB in men (79.2%)/15 GSB (20.8%) in women. Mean age 68.1 +/- 12.1 years. Mean LV EF 29.6 +/- 8.9%. 22 GSB in diabetic patients (30.6%). Ischemic etiology of ES in 41 cases (56.9%). Monomorphic ventricular tachycardia dominated among arrhythmias with 53 cases ( 73.6%). Betablocker and amiodarone were administered in 67 and 56 cases, respectively ( 93.1 and 77.8%). A statistically significant decrease of 87.7% in ventricular arrhythmias treated with shock ICD or ATP was seen ( decrease from 57.2 to 1.43 episodes 48 hours before vs. 48 hours after GSB, p<.0001) (Table 1). Hemodynamically unstable patients on continuous catecholamines responded significantly less to the two-step algorithm, including GSB. Horner's syndrome and other demographic and medication parameters did not appear to predict a better response to GSB (Table 2 ). No serious adverse events were observed. In one case, intermittent ( couple hours) vocal chord paresis after bilateral GSB has been observed. Conclusion: The two-stage algorithm for the treatment of ES, including ganglion stellate blockade, has shown stable high efficacy over the years with exceptional safety. However, the actual efficacy must be proven in a double-blinded study to allow the widespread method to the clinical practice.